A review of biological sulfate conversions in wastewater treatment - Hao, Tian-wei; Xiang, Peng-yu; Mackey, Hamish R.; Chi, Kun; Lu, Hui; Chui, Ho-kwong; van Loosdrecht, Mark C.M.; Chen, Guang-Hao (Water research (Oxford), 2014)
Treatment of waters contaminated with sulfur containing compounds (S) resulting from seawater intrusion, the use of seawater (e.g. seawater flushing, cooling) and industrial processes has become a challenging issue since around two thirds of the world's population live within 150 km of the coast. In the past, research has produced a number of bioengineered systems for remediation of industrial sulfate containing sewage and sulfur contaminated groundwater utilizing sulfate reducing bacteria (SRB). The majority of these studies are specific with SRB only or focusing on the microbiology rather than the engineered application. In this review, existing sulfate based biotechnologies and new approaches for sulfate contaminated waters treatment are discussed. The sulfur cycle connects with carbon, nitrogen and phosphorus cycles, thus a new platform of sulfur based biotechnologies incorporating sulfur cycle with other cycles can be developed, for the removal of sulfate and other pollutants (e.g. carbon, nitrogen, phosphorus and metal) from wastewaters. All possible electron donors for sulfate reduction are summarized for further understanding of the S related biotechnologies including rates and benefits/drawbacks of each electron donor. A review of known SRB and their environmental preferences with regard to bioreactor operational parameters (e.g. pH, temperature, salinity etc.) shed light on the optimization of sulfur conversion-based biotechnologies. This review not only summarizes information from the current sulfur conversion-based biotechnologies for further optimization and understanding, but also offers new directions for sulfur related biotechnology development.